Lightweight digital trust architectures in the Internet of medical things (IoMT) - Bhattacharya, Pronaya; Dutta, Pushan Kumar; Hassan, Ahdi 1991-; Sagayam, Martin; Tikadar, Subrata (IGI Global, 2024)
This book explores the current state of Lightweight Digital Trust Architectures in the Internet-of-Medical Things (IoMT) and their role in protecting sensitive patient data.
Keywords: Artificial intelligence -- Medical applications; Internet of things -- Security measures; Medical informatics -- Security measures